2020
DOI: 10.31004/prepotif.v4i2.923
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pelatihan Balut Bidai Terhadap Pengetahuan Pada Mahasiswa/I Keperawatan Stikes Tri Mandiri Sakti Bengkulu

Abstract: ABSTRACT Splint Dressing (Fixation) is a general treatment of extremity trauma or immobilization from the site of trauma such as splinting (spalk) to maintain the position of broken bones so as not to move and prevent contamination and complications. Formulation of problem in this study was whether there is Effect of Splint Dressing (Fixation) Training to Knowledge Students of Nursing at STIKES Tri Mandiri Sakti Bengkulu. The aims of this study was to determine Effect of Splint Dressing (Fixation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
3
0
5
Order By: Relevance
“…Another study explained that the effect of splint dressing training on the knowledge and skills of adolescent red cross (PMR) students at SMAN 4 Bengkulu City after being given splint dressing health education showed that the average respondent had sufficient knowledge in the category of 19 respondents (57.6%). Moreover, respondents' skills after being given health education in splints on average in the good category of 20 respondents (60.6%) (Listiana & Oktarina, 2019). Another study showed that the average value of attitudes towards preventing dengue hemorrhagic fever before giving health promotion through the video method was 49.61 and the average value of attitudes after being given an intervention through health promotion videos was 59.14 (Aisyiah et al, 2021).…”
Section: The Level Of the Knowledge Level Of Splint Dressing After Sp...mentioning
confidence: 99%
“…Another study explained that the effect of splint dressing training on the knowledge and skills of adolescent red cross (PMR) students at SMAN 4 Bengkulu City after being given splint dressing health education showed that the average respondent had sufficient knowledge in the category of 19 respondents (57.6%). Moreover, respondents' skills after being given health education in splints on average in the good category of 20 respondents (60.6%) (Listiana & Oktarina, 2019). Another study showed that the average value of attitudes towards preventing dengue hemorrhagic fever before giving health promotion through the video method was 49.61 and the average value of attitudes after being given an intervention through health promotion videos was 59.14 (Aisyiah et al, 2021).…”
Section: The Level Of the Knowledge Level Of Splint Dressing After Sp...mentioning
confidence: 99%
“…Dimana kegiatan utama dari ekstrakulikuler PMR ini adalah Pertolongan Pertama. Faktor utama yang terdapat pada pelatihan Pertolongan Pertama bagi siswa sekolah dapat memperoleh pengetahuan dan keterampilan yang diperlukan untuk melakukan pertolongan pertama pada korban, yang merupakan salah satu kompetensi dasar yang harus dimiliki oleh siswa sekolah dalam memberikan bantuan yang efektif dalam situasi yang darurat (Listiana, 2019).…”
Section: Pendahuluanunclassified
“…Pertolongan balut bidai dapat dilakukan oleh semua orang awam yang terlatih. Salah satu orang awam yang terlatih disekolah yaitu siswa yang telah mendapatkan pendidikan dasar kegawatdaruratan melalui kegiatan ekstrakurikuler Palang Merah Remaja (PMR), dan seharusnya pendidikan dasar kegawatdaruratan tidak hanya diberikan kepada anggota PMR tetapi juga semua siswa disekolah [1].…”
Section: Pendahuluanunclassified